PENGARUH MANAJEMEN KONFLIK TERHADAP PRODUKTIVITAS KERJA KARYAWAN (STUDI KASUS PADA RUMAH JAHIT K’-ONK (RJK) DI KABUPATEN PAMEKASAN) - Ummi Wahyuni; Alfi Hasaniyah (J-MACC, 2019)
The k'-onk sewing house is one of the companies engaged in sewing and computer embroidery and screen printing that is able to provide services for the community to be quickly creative and able to compete in the expansion area so that it is comprehensive in Indonesia. The type of research used in this study is associative research or relationship research. The type of data used is a type of quantitative data which is a research that is demanded to use numbers, besides that in quantitative research there is also data in the form of qualitative information. The data sources used are primary data obtained from questionnaires and secondary data obtained from other sources. Processing and data analysis techniques use multiple regression regression with the test hypothesis f and t test on the variables studied. The results showed that the internal Conflict Management variable (X1) and External Conflict Management (X2) had a positive effect on Employee Productivity (Y). And the dominant influence is the Internal Conflict Management variable (X1). The results of the study using R square with a value of 0.687 which means that conflict management has an effect of 68.7% on employee performance and the rest (100% - 68.7% = 31.3%) is influenced by other factors not examined in this study .